Daratumumab for systemic AL amyloidosis: prognostic factors and adverse outcome with nephrotic-range albuminuria - Kimmich, Christoph; Terzer, Tobias; Benner, Axel; Dittrich, Tobias; Veelken, Kaya; Carpinteiro, Alexander; Hansen, Timon; Goldschmidt, Hartmut; Seckinger, Anja; Hose, Dirk; Jauch, Anna; Wörner, Stefan M.; et al. (Blood, 2020)
Daratumumab has shown promising first results in systemic amyloid light-chain (AL) amyloidosis. We analyzed a consecutive series of 168 patients with advanced AL receiving either daratumumab/dexamethasone (DD, n = 106) or daratumumab/bortezomib/dexamethasone (DVD, n = 62). DD achieved a remission rate (RR) of 64% and a very good hematologic remission (VGHR) rate of 48% after 3 months. Median hematologic event-free survival (hemEFS) was 11.8 months and median overall survival (OS) was 25.6 months. DVD achieved a 66% RR and a 55% VGHR rate. Median hemEFS was 19.1 months and median OS had not been reached. Cardiac organ responses were noted in 22% with DD and 26% with DVD after 6 months. Infectious complications were common (Common Terminology Criteria [CTC] grade 3/4: DD 16%, DVD 18%) and likely related to a high rate of lymphocytopenia (CTC grade 3/4: DD 20%, DVD 17%). On univariable analysis, hyperdiploidy and gain 1q21 conferred an adverse factor for OS and hemEFS with DD, whereas translocation t(11;14) was associated with a better hemEFS. N-terminal prohormone of brain natriuretic peptide >8500 ng/L could not be overcome for survival with each regimen. Multivariable Cox regression analysis revealed plasma cell dyscrasia (difference between serum free light chains [dFLC]) >180 mg/L as an overall strong negative prognostic factor. Additionally, nephrotic-range albuminuria with an albumin-to-creatinine-ratio (ACR) >220 mg/mmol was a significantly adverse factor for hemEFS (hazard ratio, 2.1 and 3.1) with DD and DVD. Daratumumab salvage therapy produced good results and remission rates challenging any therapy in advanced AL. Outcome is adversely influenced by the activity of the underlying plasma cell dyscrasia (dFLC) and nephrotic-range albuminuria (ACR).